Pengaruh Virtual Account Billing, Payment Transaction, Dan E-Statement Terhadap Pengaplikasian M-Banking Dengan User Friendly Sebagai Variabel Moderasi ( Survei Pengguna M-Banking BNI Mahasiswa UNISRI) - Elkana Fitria Sari; Hudi Kurniawanto (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze the effect of Virtual Account Billing, Payment Transaction, and E-Statement on the application of BNI m-banking, with user friendly as a moderating variable. The population in this study were students of Slamet Riyadi University Surakarta around 7,316 students. The sample in this study used a purposive sampling method and obtained a sample of 181 students. The data analysis techniques used were descriptive analysis, multiple linear regression analysis, t-test, F-test, determination coefficient test (R2), and moderated regression analysis (MRA). The questionnaire in this study was tested for validity and reliability, the results were valid and reliable, and met the classical assumption test. The results of the study with multiple linear regression analysis showed that virtual account billing, payment transactions, and e-statements had a significant positive effect on the application of m-banking by students of Slamet Riyadi University Surakarta. The results of the moderated regression analysis (MRA) show that user friendly does not moderate between virtual account billing and payment transactions on the application of m-banking by students of Slamet Riyadi University Surakarta, but user friendly moderates between e-statement on the application of m-banking by students of Slamet Riyadi University Surakarta